ἌΦΕΣΙΣ In The New Testament And Its Suggested Links To The Biblical Jubilee - Christopher James Luthy (Jurnal Jaffray, 2019)
This study responds to the claims that the term ἄφεσις (usually translated “forgiveness”) should be understood in light of the biblical Jubilee. The study commences with a brief survey of the word’s use in the Septuagint and Classical Greek literature, alongwith the related verb ἀφίημι. It then examines each use of ἄφεσις in the New Testament. Texts in Matthew, Mark, Luke-Acts, Paul’s writings and Hebrews are examined, with a particular focus on Lucan texts (since these contain the majority of the occurrences of the word). The study concludes that the verb ἀφίημι was never explicitly connected to the Jubilee in the Septuagint, so there is no reason to view the word in this light in the New Testament. The study also concludes that even though the term ἄφεσις had Jubilee connotations at the time the Septuagint was written, there was significant semantic development such that by the time of the New Testament, the word had a distinct and unambiguous meaning, centred on the forgiveness of sins and unrelated to the Jubilee.